take your first bracket take the 4 and multiply with everything in the bracket.
therefore 4*-3x=-12x
then 4*-5=-20
then in the second one you just have a minus so multiply that with everything in the bracket -1*10=-10
-1*4x=-4x
therfore everthing =-12x-20-10-4x
now you just add all the single numbers together and all the x`s together known as like terms.
-12x-4x=-16x
-20-10=-30
therefor =-16x-30
simiraraly for question b
-2+x-18-24x-12
=-32-23x
remeber a minus times a minus is a plus.
2007-10-10 19:56:18
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
A)4(-3x-5)-(10+4x)=
(-12x-20)-(10+4x)=
-12x-20-10-4x=
-16x-30.
B)-(2-x)-3(6+8x)-12=
-2+x-18-24x-12=
x-24x-2-18-12=
-23x-32.
thats the answer.when you expand(open up) -(2-x),
the - outside the bracket represent -1.so when you expand it inside,it will become -2+x. it's like (-1 times 2) + (-1 times -x).
2007-10-10 21:19:54
·
answer #2
·
answered by dark 3
·
0⤊
0⤋
1st,expand the all the terms in the parenthesis.
Eg:a(b+cx)=a*b+a*cx
=ab+acx
2ndly,Group all the like terms together
3rdly,carry out normal computation with like term
4th,factorise the expression(LCM) till it simplest form.
(-)*(-)=(+)
(-)*(+)=(-)
(+)*(-)=()
(+)*(+)=(+)
a)4(-3x-5)-(10+4x) =-12x-20-10-4x
=-12x-4x-20-10
=-16x-30
=-2(8x+15)
b)-(2-x)-3(6+8x)-12=-2+x-18-24x-12
=-2-18-12+x-24x
=-32-23x
= -(32+23x)
2007-10-10 21:08:58
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Don`t panic!
Question a.
- 12x - 20 - 10 - 4x
- 16x - 30
Question b.
- 2 + x - 18 - 24x - 12
- 32 - 23x
2007-10-10 20:25:07
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
4(-3x-5)-(10+4x) =
simplify first the expressions between main signs:
4(-3x-5)= -12x-5x
(10+4x) you don't need to simplify
then solve using the main sign:
-12x-5x-10+4x
add the like variables:
-12x-5x-4x so that is equal to -21x
just add the whole number left and thta is the answer
-21x+10
when answering expressions like this, you just need to solve the expressions first that are in a parentheses. and don't forget the MDAS rule:
think you can do the other
2007-10-10 19:59:36
·
answer #5
·
answered by charlons 1
·
0⤊
1⤋
I'll go over the first one.
4 (-3x - 5) - (10 + 4x)
-12x - 20 - 10 - 4x
-16 x - 10
2007-10-10 19:49:27
·
answer #6
·
answered by Howard H 7
·
0⤊
1⤋
. 4(-3x-5)-(10+4x) =
first do the first set of parenthesis which is 4(-3x-5). to do that, you multiply 4 times -3 and then multiply that number, which is -12x to -5 to get 60x. then do the other set the same way: 10+4x = 14x. finally, you just subtract 60x - 14x and you get 46x.
-(2-x)-3(6+8x)-12=
with this one, you do -2-x-3 times 14x-12
then you get -2+(-x)+(-3)14x-12
next, you group together like-terms. -2x+-3 times 14x-12
that brings you to: -28x+-15. since there are no more like-terms, you're done.
2007-10-10 20:32:46
·
answer #7
·
answered by neji_hyuga1241 1
·
0⤊
1⤋
It's in simplest form when it can't be broken down any more. For example, if you have 4b^2+2b it could be simplified to 2b(2b+1) and that can't be broken down anymore! Good Luck!
2016-05-21 03:47:42
·
answer #8
·
answered by dorinda 3
·
0⤊
0⤋
a. -16x-30
b. -32-23x
i don't know how to explain step by step, but if all goes wrong and you still can't figure it out try this website out
http://quickmath.com
2007-10-10 19:52:29
·
answer #9
·
answered by rose 2
·
0⤊
1⤋